CORRELATION BETWEEN HIGH-PURINE DIET PATTERNS AND URIC ACID LEVELS AMONG THE ELDERLY IN PASURUAN REGENCY - Setyawan, Yuswanto (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Hyperuricemia is a common metabolic disorder among the elderly and is closely associated with gout, renal impairment, and cardiovascular disease. A high-purine diet is one of the major modifiable factors influencing serum uric acid levels, yet evidence among Indonesian older adults remains limited. This study aimed to examine the correlation between high-purine dietary patterns and serum uric acid levels among elderly individuals in Pasuruan Regency, East Java. A cross-sectional analytic observational design was applied to 120 respondents aged ≥60 years, selected using a simple random sampling technique. Data were obtained through structured interviews, a validated Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and laboratory testing of serum uric acid levels. The results revealed a moderate positive correlation between the High-Purine Diet Score (HPDS) and serum uric acid concentration (r=0.42; p<0.001). The overall prevalence of hyperuricemia was 23.3%, with the highest proportion (37.5%) observed among participants with high HPDS. The study concludes that higher purine intake is significantly associated with elevated serum uric acid levels in the elderly, emphasizing the need for dietary counseling and public health interventions focused on balanced nutrition in older populations.